Rhinoscleroma-A Rare Granulomatous Disease in a Child (Indian Journal of Forensic Medicine & Toxicology, 2020)
Rhinoscleroma (RS) is a chronic granulomatous disease caused by Klebsiella rhinoscleromatis. In all thepatients, the nose is affected but sometimes extends to any parts of the airways. Diagnosis of this disease isdone on the basis of the histopathological examination or direct evidence of the bacteria in nasal exudates.The differential diagnoses of the RS are syphilis, malignancy and midline granuloma. Streptomycin is drugof choice, although fluoroquinolones and cephalosporin also provide good results. Surgery is opted in caseof obstruction or deformity. Here, we reported a case of 11-year girl diagnosed as RS on the basis of thehistopathological examination. This case was treated by endoscopic removal of the mass in the nasal cavityfollowed by a course of ciprofloxacin. She was found asymptomatic at the last visit of 1 year after treatmentand there was no evidence of recurrence.
Keywords: Rhinoscleroma, nasal cavity, pediatric patient,Mikulicz cells, Russel bodies.